Developing think-pair-share learning activities to enhance grade 3 students’ academic achievement on mixed operations of addition, subtraction, multiplication, and division - Teerada Chaisena; Titiworada Polyiem (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
Primary students’ understanding of mixed arithmetic operations is essential for building foundational mathematical competence, and cooperative learning strategies such as think–pair–share (TPS) may enhance both conceptual understanding and classroom engagement. The purposes of this study were to (1) develop think–pair–share learning management plans based on the 70/70 efficiency criterion, (2) compare grade 3 students’ academic achievement before and after the intervention, and (3) examine students’ satisfaction with the learning activities. The participants were 19 of grade 3 students selected through cluster random sampling from a primary school in Roi Et Province, Thailand. The instruments included 13 TPS learning management plans, a 20-item mathematics achievement test, and a 15-item student satisfaction questionnaire. The data were analyzed using efficiency analysis, descriptive statistics, and dependent t-test. The results showed that the instructional plans achieved an efficiency of 72.86/76.60, students’ posttest scores were significantly higher than pretest scores with a very large effect size, and overall student satisfaction was at a very high level. This study contributes empirical evidence supporting the effectiveness of structured cooperative learning in enhancing primary mathematics achievement.